Metode Task-Based, Communicative, dan ICT dalam Pembelajaran Bahasa Arab - Sugino, Sugino; Rohana, Rohana; Waslam, Waslam; Iis, Susiawati (FKDP (Forum Komunikasi Dosen Peneliti), 2025)
Arabic language learning has undergone substantial transformation due to shifts in pedagogical paradigms and the rapid advancement of digital technology. These changes highlight the need for instructional models that integrate communicative competence, authentic task performance, and the strategic use of technological tools. This study aims to analyze the concepts and implementations of Task-Based Language Teaching (TBLT), Communicative Language Teaching (CLT), and Information and Communication Technology (ICT) in contemporary Arabic language learning, as well as to examine the potential synergy among these three approaches as an integrative instructional model. Employing a literature review design, this study collected data from peer-reviewed journal articles, academic books, and verified research reports published between 2014 and 2025. Data were analyzed through reduction, thematic categorization, and narrative synthesis. The findings reveal that TBLT promotes meaningful language use through authentic tasks, CLT enhances communicative competence through natural interaction, and ICT enriches learning experiences by providing flexible access to digital resources. The synthesis further indicates that integrating these approaches offers a more effective and adaptive model for Arabic language instruction, aligned with the needs of digital-age learners. This study contributes theoretically to applied linguistics and provides practical implications for teachers and curriculum developers seeking innovative and relevant approaches to Arabic language education.